2016
DOI: 10.1111/joa.12430
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional reconstruction of Haversian systems in human cortical bone using synchrotron radiation‐based micro‐CT: morphology and quantification of branching and transverse connections across age

Abstract: This study uses synchrotron radiation-based micro-computed tomography (CT) scans to reconstruct three-dimensional networks of Haversian systems in human cortical bone in order to observe and analyse interconnectivity of Haversian systems and the development of total Haversian networks across different ages. A better knowledge of how Haversian systems interact with each other is essential to improve understanding of remodeling mechanisms and bone maintenance; however, previous methodological approaches (e.g. se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 58 publications
7
95
0
1
Order By: Relevance
“…; Maggiano et al. ) and this level of resolution could add new information if used in future studies. Previous research has shown that in vivo micro‐CT can be used to image cortical canals in live rats (Harrison & Cooper, ; Pratt et al.…”
Section: Discussionmentioning
confidence: 97%
“…; Maggiano et al. ) and this level of resolution could add new information if used in future studies. Previous research has shown that in vivo micro‐CT can be used to image cortical canals in live rats (Harrison & Cooper, ; Pratt et al.…”
Section: Discussionmentioning
confidence: 97%
“…In that study, Lanyon and Bourn (1979) (Cohen and Harris, 1958;Maggiano et al, 2016) will be needed because the current capacity of high-resolution 3D computed tomography is not sufficiently accurate (Hennig et al, 2015). In that study, Lanyon and Bourn (1979) (Cohen and Harris, 1958;Maggiano et al, 2016) will be needed because the current capacity of high-resolution 3D computed tomography is not sufficiently accurate (Hennig et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…; Maggiano et al. ) and therefore are not a pathological or otherwise ischemia‐related infilling of the Haversian canal with bone tissue. Recent 3D studies suggest the possibility that sealed osteons represent the closing cones of normal secondary osteons.…”
Section: Discussionmentioning
confidence: 98%
“…3). Within the past 10 years, several studies have described sealed osteons in secondary bone (Pazzaglia et al 2010(Pazzaglia et al , 2013(Pazzaglia et al , 2015Congiu & Pazzaglia, 2011;Maggiano et al 2016), yet none has conclusively demonstrated their origin.…”
Section: Introductionmentioning
confidence: 99%